2021
DOI: 10.3389/fonc.2021.697198
|View full text |Cite
|
Sign up to set email alerts
|

A Pyroptosis-Related Gene Signature for Predicting Survival in Glioblastoma

Abstract: BackgroundIn this study, a prognostic model based on pyroptosis-related genes was established to predict overall survival (OS) in patients with glioblastoma (GBM).MethodsThe gene expression data and clinical information of GBM patients were obtained from The Cancer Genome Atlas (TCGA), and bioinformatics analysis of differentially expressed genes was performed. LASSO Cox regression model was used to construct a three-pyroptosis-related gene signature, and validation was performed using an experimental cohort.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…Therefore, CAFs have become a new target for tumor therapy. For example, inhibition of tumor progression by targeting and regulating CAFs or overcoming their barrier Previous studies have demonstrated the role of the tumor microenvironment, especially the immune microenvironment, in tumor biology (Sumida et al, 2011;Xu et al, 2020;Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CAFs have become a new target for tumor therapy. For example, inhibition of tumor progression by targeting and regulating CAFs or overcoming their barrier Previous studies have demonstrated the role of the tumor microenvironment, especially the immune microenvironment, in tumor biology (Sumida et al, 2011;Xu et al, 2020;Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the role of the tumor microenvironment, especially the immune microenvironment, in tumor biology ( Sumida et al, 2011 ; Xu et al, 2020 ; Li et al, 2021 ). Results of the present study showed that the identified DEGs were mainly enriched in immune-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…18 Besides, DFNA5/ GSDME acted as an antioncogene in hepatocellular cancer, and loss of DFNA5/GSDME contributed to drug resistance in melanoma and lung cancer. [19][20][21] Signatures based on pyroptosis showed substantial prognostic predictive values in ovarian cancer, 22 glioblastoma, 23 melanoma, 24 and gastric cancer, 25 but pyroptosis-related signatures on BC are lacking. Besides, pyroptosis was identified in many types of immune cells, but the potential function of pyroptosis in the tumour immune microenvironment (TIME) remains undefined.…”
mentioning
confidence: 99%
“… 43 , 44 At the same time, Li, X.Y et al found that there was a close relationship between CASP4 and glioblastoma. 45 Concluding the results of survival analysis, independent prognosis analysis, and nomogram, we found that the risk signature had the accurate effectiveness for predicting survival of patients.…”
Section: Discussionmentioning
confidence: 77%